Analysis of First In First Out (FIFO) Bandwidth Packet Queuing Technique with Random Early Detection (RED) on WLAN (Wireless LAN) - Hendrik Kusbandono; Tri Lestariningsih; MH. Ramdhani Ismar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Implementation of bandwidth usage is generally only optimally utilized by some WLAN network users; this is often influenced by the monopoly use of bandwidth capacity for both download and upload. The aim is to determine the optimal packet queuing technique based on QoS parameters in WLAN network implementation. This research method uses QoS FIFO and RED packet queuing techniques with throughput, delay, jitter, and packet loss parameters on WLAN networks. Quality of Service (QoS) results on queuing methods using FIFO parameters (throughput 79.65%, delay 73.43 ms, jitter 82.21 ms, and packet loss 3.39%) RED technique throughput parameters: 79.29% delay (75.35 ms), jitter (71.45 ms), and packet loss (7.17%). QoS, compared to FIFO and RED queuing techniques, both perform well in maintaining the quality of network services. The FIFO queuing technique has an average index value of 3.5 with